2017
DOI: 10.1002/jcp.26037
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow adipocytes support hematopoietic stem cell survival

Abstract: In bone marrow (BM), hematopoietic elements are mingled with adipocytes (BM-A), which are the most abundant stromal component in the niche. BM-A progressively increase with aging, eventually occupying up to 50% of BM cavities. In this work, the role played by BM-A was explored by studying primary human BM-A isolated from hip surgery patients at the molecular level, through microarray analysis, and at the functional level, by assessing their relationship with primary human hematopoietic stem cells (HSC) by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 36 publications
6
84
2
2
Order By: Relevance
“…This conclusion is supported by unbiased proteomic approaches that indicate a seemingly unidentified cholesterol-oriented metabolism. In contrast to our results, a recent transcriptomic study comparing gene expression of human BM-Ad isolated from the femoral head and SC-Ad show that genes over-represented in human BM-Ad participate in signaling pathways without clear differences in the enzymes involved in lipid metabolism (such as cholesterol metabolism and TG hydrolysis) (Mattiucci et al, 2018). In addition, this report found decreased adiponectin expression, which stand in contrast to our current results and another study that identified BM-Ad as an important source of adiponectin (Cawthorn et al, 2014).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This conclusion is supported by unbiased proteomic approaches that indicate a seemingly unidentified cholesterol-oriented metabolism. In contrast to our results, a recent transcriptomic study comparing gene expression of human BM-Ad isolated from the femoral head and SC-Ad show that genes over-represented in human BM-Ad participate in signaling pathways without clear differences in the enzymes involved in lipid metabolism (such as cholesterol metabolism and TG hydrolysis) (Mattiucci et al, 2018). In addition, this report found decreased adiponectin expression, which stand in contrast to our current results and another study that identified BM-Ad as an important source of adiponectin (Cawthorn et al, 2014).…”
Section: Resultscontrasting
confidence: 99%
“…However, it is unclear whether these differentiated cells recapitulate the phenotype of mature human primary BM-Ad. These in vitro studies suggest a role for BM-Ad in hematopoiesis regulation (Mattiucci et al, 2018; Naveiras et al, 2009), bone remodeling (Hardaway et al, 2015) and cancer progression (Diedrich et al, 2016; Herroon et al, 2013; Liu et al, 2015; Shafat et al, 2017; Tabe et al, 2017). These issues highlight that our knowledge of the physiological phenotype of primary BM-Ad remains limited.…”
Section: Introductionmentioning
confidence: 92%
“…Adipocytes in the bone marrow serve critical roles, regulating homeostasis in hematopoietic niches (63,64) and storing energy for use during exercise. (17) An increase in marrow fat is found during conditions associated with osteoporosis-aging and estrogen deficiency (12) -and the same has been suggested in the unique bone fragility that accompanies caloric restriction.…”
Section: Discussionmentioning
confidence: 99%
“…To determine if similar differences occur in humans, we next analysed the transcriptomes of adipocytes isolated from human femoral BMAT and subcutaneous WAT, which our previous analyses revealed to be globally distinct (Mattiucci et al, 2018). Consistent with our findings in rabbits, human BMAds were not enriched for brown or beige markers and had decreased expression of genes relating to glucose metabolism and insulin responsiveness (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1E, Supplemental Fig. 2A-B), ethical approval and subject characteristics are as described previously (Mattiucci et al, 2018). For human subjects in cohort 2 (Fig.…”
Section: Methodsmentioning
confidence: 99%